Herbicides as Weed Control Agents: State of the Art: I. Weed Control Research and Safener Technology: The Path to Modern Agriculture. Issue 3 (7th August 2014) - Kraehmer, Hansjoerg; Laber, Bernd; Rosinger, Chris; Schulz, Arno
Abstract : The development of weed control and safeners and of screening tools to find them has evolved substantially over the past 100 years . Abstract: The purpose of modern industrial herbicides is to control weeds. The species of weeds that plague crops today are a consequence of the historical past, being related to the history of the evolution of crops and farming practices. Chemical weed control began over a century ago with inorganic compounds and transitioned to the age of organic herbicides. Targeted herbicide research has created a steady stream of successful products. However, safeners have proven to be more difficult to find. Once found, the mode of action of the safener must be determined, partly to help in the discovery of further compounds within the same class. However, mounting regulatory and economic pressure has changed the industry completely, making it harder to find a successful herbicide. Herbicide resistance has also become a major problem, increasing the difficulty of controlling weeds. As a result, the development of new molecules has become a rare event today.